187 The Impact of Electronic Pathways and Digital Systems on Neck of Femur Fracture Outcomes: A Systematic Review. (19th August 2022) - Tandon, D; Curlewis, K; Vusirikala, A; Subramanian, P; Patel, A
Abstract: Aim: Electronic pathways and digital systems are novel interventions in medicine that include clinical decision support systems and checklists for care delivery. The primary aim of this systematic review was to outline the impact of electronic pathways and digital systems on neck of femur (NOF) fracture outcomes as according to Best Practice Tariff (BPT) outcomes. Method: A literature search was conducted using the PubMed, Cochrane Library and MEDLINE databases. Studies were included for review if they addressed the impact of an electronic pathway or digital system on at least one of the BPT outcome measures. Studies were excluded from the review if they were not written in English. After 698 citations were independently reviewed by two authors, 6 papers were included for full text review. The data was significantly heterogenous, hence a narrative synthesis was performed. Risk of bias for each paper was assessed using the Downs and Black scale. Results: Time to theatre, length of hospital stay and management of osteoporosis for secondary fracture prevention displayed statistically significant improvements. Mortality and post-operative complications demonstrated non-significant improvements. No outcome measures were adversely affected. The identified studies had a similar risk of medium bias. Conclusions: Electronic pathways and digital systems have a statistically significant positive impact on several NOF fracture outcomes. Due to the novel nature of electronic pathways and digital systems in orthopaedics, a limited number of studies were identified for review. More high-quality homogenous prospective cohort studies are required to allow for a meta-analysis.